The Role of Social Services at the Payung Besurek Elderly Social Welfare Institution in Improving the Quality of Life of Older Adults - Eka Putra; Meriyanto (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2026)
The Payung Besurek Elderly Social Welfare Institution (LKS-LU) plays a role in providing social services to improve the quality of life of older adults. This study aims to examine the role of social services in enhancing the quality of life of older adults at LKS-LU Payung Besurek. A qualitative descriptive method was employed, involving data collection, processing, and analysis to draw conclusions relevant to the research objectives. The study involved six older adults, one institutional head, and one social worker. The findings indicate that LKS-LU Payung Besurek provides various social services, including case outreach and response, service advocacy and fulfillment of basic needs for older adults, individual social care, group capacity building, strengthening family roles in elderly welfare, social rehabilitation programs (Elderly Center/Teras Lansia), and productive economic activities for older adults. The study reveals that social services play an important role in improving the quality of life of older adults. These findings are consistent with social welfare concepts emphasizing the importance of fulfilling needs and providing social support for vulnerable groups. The holistic services provided by LKS-LU Payung Besurek help older adults live better and more meaningful lives. This study is expected to serve as an evaluation and development reference for elderly social welfare institutions.